Bilingual education in Nunavut: Trojan horse or paper tiger? - Andrew Peter Hodgkins (Canadian Society for Studies in Education, 2010)
On April 1 2009, Nunavut celebrated its tenth anniversary as Canada's newest territory. Now halfway through the timeline set to fulfill its original goals, Nunavut is beginning to implement its new Education Act. This paper analyses education policy in the territory by specifically examining Berger's (2006) influential report, The Nunavut Project, which forms a basis for the new Education Act. Berger promoted the idea that achieving bilingual education in the K-12 system is required in order to improve graduation rates and increase Inuit participation in the wage economy. The paper provides both critical insights into Nunavut's struggles for self-determination, and a case study for other regions currently engaged in the arduous path towards decolonisation.